An Examination On E-Banking Service Quality And Its Significance On E-Satisfaction And E-Loyalty: An Asian Study - Prithviraj Malnaad,; Abdul Rahman S Senathirajah,; Gan Connie,; Zahir Osman,; Rasheedul Haque, (ASR Research India, 2022)
This research aims to explore the importance of e-service quality dimensions in an e-banking atmosphere by providing a review of how e-service quality perceptions have evolved through the continuing stream of change in banking technology. This paper also helps to ascertain the complex relationship between e-service quality, customer satisfaction and the customer loyalty amongst e-banking customers. Data were collected from an online survey, based on the responses of 376 online customers of different banks, the “Structural Equation Modelling”(SEM) techniques was used to test the “reliability and validity” of the suggested model. The analysis was performed on the service quality dimensions from the SERVQUAL scale. The study re-examines traditional service quality in the e-banking era and the findings are important to have a better understanding of customers’ perception of service quality of internet banking and consequently on how to improve their satisfaction with respect to the online aspects of service quality. (Abstract by authors)